THE ROLE OF THE QUR'AN AS A SOURCE OF KNOWLEDGE IN SHAPING A TAWHID-BASED ISLAMIC EDUCATION CURRICULUM AND FILIAL PIETY TOWARD PARENTS: AN ANALYSIS OF QUR’AN SURAH AL-BAQARAH VERSE 133 AND SURAH AL-ISRA’ VERSE 23 - Fatimah Azzahro; Fenny Syaichie Savawia; Ahmad Yusam Thobroni (Yayasan Amanah Nur Aman, 2026)
Curriculum development is fundamentally grounded in three main aspects: philosophical, sociological, and psychological dimensions. However, reliance solely on these three aspects may cause the curriculum to lose its spiritual dimension, which constitutes an essential element of education. Therefore, the integration of Islamic values derived from the Qur’an and Hadith is necessary as a foundation for constructing a more comprehensive and meaningful curriculum. This study aims to examine the role of the Qur’an as a basis for the formation of the Islamic education curriculum by referring to Qur’an Surah Al-Baqarah verse 133 and Surah Al-Isra’ verse 23. The study employs a qualitative library research method utilizing contemporary literature combined with interpretative approaches from classical Islamic scholars. The collected data were analyzed descriptively to generate relevant conclusions. The findings reveal that the Qur’an possesses strong relevance as a foundational framework for curriculum development in the contemporary era. Surah Al-Baqarah verse 133 emphasizes the establishment of a strong foundation of tawhid (Islamic monotheism), while Surah Al-Isra’ verse 23 highlights the obligation to honor and show devotion to one’s parents. A curriculum that incorporates these two teachings is expected to shape students with a strong tawhidic foundation, enabling them to resist secular influences. Furthermore, the value of filial piety toward parents can foster students’ appreciation for the significant role and existence of both parents. This study affirms that the Qur’an serves as the primary universal guideline that remains relevant across all times and places (shalih li kulli zaman wa makan).